Causes and climatic influence of centennial-scale denitrification variability in the southeastern Arabian Sea since the last glacial period. (May 2021) - Nagoji, Sidhesh; Tiwari, Manish
Abstract: Denitrification occurring in the oxygen minimum zone of the Arabian Sea produces nitrous oxide, a powerful greenhouse gas. Therefore, it is important to understand the mechanisms controlling denitrification's intensity and evaluate its influence on the global climate at various timescales. We studied multiple geochemical and isotopic proxies in a sediment core from the southeastern Arabian Sea (SEAS) at a high (centennial-scale) resolution. We find that since the last glacial period, both the ventilation and the productivity caused by the South Asian summer monsoon played a major role in controlling the denitrification variability in SEAS. During the Last Glacial Maximum (LGM) and since the Holocene, denitrification increased in SEAS despite reduced monsoon-induced productivity. During the LGM, weakened thermohaline circulation resulted in reduced ventilation of the intermediate waters of SEAS, causing increased denitrification. During the Holocene, the increase in denitrification is caused by an enhanced inflow of oxygen-depleted Red Sea and Persian Gulf waters into the intermediate depth of SEAS owing to a rising sea level that prohibited ventilation by the Antarctic Intermediate Water. We further find millennial-scale synchronicity between denitrification in SEAS, global monsoons, and the North Atlantic climate, implying systematic linkages via greenhouse gases abundance.